SIMULASI PERGERAKAN PENGGUNA AKSES DARAT MASUK DAN KELUAR BANDAR UDARA - Syahrian Wirawan, Muhammad
Soekarno-Hatta International Airport became the 25th largest airport in the world with a total number of passengers of 54,49,626 pax in 2019. Projecting the numbers will grow, the operator of the airport commits themselves to developing the airport’s infrastructure. However, this development is often not accompanied by the development of airport ground access which could affect the effectivity of airport ground access in connecting passengers to airport’s terminals. One of the methods that can be used to quantify the possible affect received by land access due to the development of airport infrastructure to handle aircraft flight traffic is discrete-event simulation. With discrete-event simulations, a system such as airport land access to the terminal can be modelled to describe the process of ground transportation movement. Discreteevent simulation can also provide an overview of the behavior of the system and facilitate evaluations if there are factors that hinder the system from operating in optimal conditions. This research resulted in a simulation model of the ground access system of Terminal 3 of Soekarno-Hatta International Airport with Matlab Simevents. In addition, this research also produces results in the form of estimation of saturated capacity, estimation of the number of entities that move through each link and node, and estimation of the processing time and delay of each link and node in the simulation model.